Efficacy of gene-therapy based on adenovirus encoding granulocyte-macrophage colony-stimulating factor in drug-sensitive and drug-resistant experimental pulmonary tuberculosis. (September 2016) - Francisco-Cruz, Alejandro; Mata-Espinosa, Dulce; Ramos-Espinosa, Octavio; Marquina-Castillo, Brenda; Estrada-Parra, Sergio; Xing, Zhou; Hernández-Pando, Rogelio
Summary: Tuberculosis (TB), although a curable disease, remains a major cause of morbidity and mortality worldwide. It is necessary to develop a short-term therapy with reduced drug toxicity in order to improve adherence rate and control disease burden. Granulocyte-macrophage colony-stimulating factor (GM-CSF) may be a key cytokine in the treatment of pulmonary TB since it primes the activation and differentiation of myeloid and non-myeloid precursor cells, inducing the release of protective Th1 cytokines. In this work, we administrated by intratracheal route recombinant adenoviruses encoding GM-CSF (AdGM-CSF). This treatment produced significant bacterial elimination when administered in a single dose at 60 days of infection with drug sensitive or drug resistant Mtb strains in a murine model of progressive disease. Moreover, AdGM-CSF combined with primary antibiotics produced more rapid elimination of pulmonary bacterial burdens than conventional chemotherapy suggesting that this form of treatment could shorten the conventional treatment.